2021
DOI: 10.3389/fpsyg.2021.731017
|View full text |Cite
|
Sign up to set email alerts
|

Late Adulthood, COVID-19-Related Stress Perceptions, Meaning in Life, and Forgiveness as Predictors of Mental Health During the COVID-19 Pandemic

Abstract: The purpose of this study was to examine multiple direct and indirect pathways of the association between older age and mental health through COVID-19-related stress perceptions, meaning in life, and forgiveness of situations. Participants were 1,382 U.S. adults who were part of the Harvard Digital Lab for the Social Sciences panel who volunteered to complete a 12 min survey in the spring of 2020. The sample had an average age of 56 years, was slightly more male (55%) than female (44%) or other (2%), mostly Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…On the other hand, it is known that some personality traits, such as optimism, are effective in individuals having the necessary emotion, thought and relationship style to forgive (McCullough et al, 1998). In fact, studies in the literature reveal that there are moderate positive correlations between the optimism of individuals and their tendency to forgive situations (Ramadhani et al, 2021; Toussaint et al, 2021). In a study conducted by Ramadhani et al (2021) on university students, it was determined that among the behaviours of forgiving oneself, others and situations, forgiveness of situations explained the variance in optimism the most.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is known that some personality traits, such as optimism, are effective in individuals having the necessary emotion, thought and relationship style to forgive (McCullough et al, 1998). In fact, studies in the literature reveal that there are moderate positive correlations between the optimism of individuals and their tendency to forgive situations (Ramadhani et al, 2021; Toussaint et al, 2021). In a study conducted by Ramadhani et al (2021) on university students, it was determined that among the behaviours of forgiving oneself, others and situations, forgiveness of situations explained the variance in optimism the most.…”
Section: Discussionmentioning
confidence: 99%
“…Although research is still ongoing, these studies seem to suggest that at least a sub-population of older adults is emotionally resilient, potentially owing to their complex experiences and adaptive coping skills/strategies built during their previous lives. Indeed, their resilience has been found to be less influenced by stressful life events ( 66 ) and associated with meaning in life ( 67 ), which may in part explain the better mental health outcomes observed in the older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Further, late adults who are better at creating meaning from their life experiences, are also expected to more easily find meaning in the face of challenging conditions, including the COVID-19 pandemic. Indeed, research has found that meaning in life enables individuals to better cope with traumatic events (e.g., cancer) and promotes posttraumatic growth (Park, 2010 ), and studies performed during the COVID-19 pandemic showed that older adults experience a stronger sense of meaning, which related to better mental health (Toussaint et al, 2021 ) or less feelings of covid-related distress (Humphrey & Vari, 2021 ).…”
Section: How Do Late Adults Experience Meaning During the Covid-19 Lo...mentioning
confidence: 99%